P0780TRENDS IN EMERGENCY DEPARTMENT USE IN PATIENTS DIAGNOSED WITH HYPERKALAEMIA: AN ANALYSIS OF A U.S. NATIONAL EMERGENCY DEPARTMENT DATABASE. (6th June 2020) - Rafique, Zubaid; Aggarwal, Saurabh; Topaloglu, Ozlem; Cornea, Georgiana; Conrad, Ansgar; Peacock, Frank
Abstract: Background and Aims: Hyperkalaemia (HK) refers to increased serum potassium concentration, with possible severe effects on health outcomes and resource utilisation. HK is prevalent in patients suffering from heart failure, chronic kidney disease (CKD) and diabetes mellitus and its risk is increased by medications, e.g. inhibitors of the renin-angiotensin-aldosterone system (RAAS). The objective of this study was to examine trends in emergency department (ED) use in patients diagnosed with HK. Method: The latest available 2016 Nationwide Emergency Department Sample (NEDS) data set from the Healthcare Cost and Utilization Project was analysed to estimate the burden of ED visits in patients with HK. Patients with an ICD-10 diagnosis code E87.5 (Hyperkalaemia) or E87.8 (Other disorders of electrolyte and fluid balance, not elsewhere classified; included due to the incidence of miscoding HK) were included. The rate of comorbidities (diabetes, CKD, heart failure and hypertension) were assessed using previously validated ICD-10 codes. Results: In 2016, there were an estimated 1, 322, 071 ED visits with a diagnosis of HK, out of which 6.7% were recorded as the primary diagnosis. The vast majority of these ED visits resulted in same hospital admission (1, 075, 492 hospital stays). The rate of ED visits and hospital admission were 409.1 and 332.8 per 100, 000 persons respectively. The mean (SE) age was 61.8 (0.21) years and 52% were male. Patients had high rate of comorbidities: diabetes 43.1%, hypertension 62.0%, CKD 44.4%, heart failure 23.1%, non-dialysis CKD 12.1% and CKD requiring dialysis 12.1%. In patients with primary diagnosis of HK, the mean (SD) hospital length of stay was 3.3 (4.2) days and total mean (SD) hospital charges were $34, 923 ($100, 435). Conclusion: Patients with HK represent an expensive health care burden, as well as suffering with high rates of comorbidities and ED visits. There is an urgent need for new treatment options in the acute setting to improve outcomes for patients with HK.